Influence of moisture content on recovery and durability of dairy manure compost pellets. (June 2022) - Alege, Femi P.; Tao, Haiying; Miito, Gilbert J.; DeVetter, Lisa W.; Ndegwa, Pius M.
Abstract: This paper presents model relationships between pre-pelleting moisture content (MC) of composted dairy manure and both pellet durability (PD) and pellets recovery (PR). Pellets were produced with two dies (6-mm and 8-mm) at MC ranging from 10 to 35% (wet basis). Results showed strong correlations between PR and PD at MC between 10 and 35% (r = 0.87 for the 8-mm die, and r = 0.98 for the 6-mm die). Regression equations also revealed PD and PR were strongly dependent on feedstock MC (r 2  = 0.96 and 0.96 for 6-mm die, and 0.94 and 0.95 for 8-mm die, respectively). Equations showing PD as functions of both PR and MC were also developed and verified. The percent of pellets recovered, therefore, may be used to predict the durability of the pellets at a given MC. The models have significant potential of reducing time and cost of producing pellets from dairy manure-composts. Graphical abstract: Unlabelled Image Highlights: Models linking pellet durability (PD), recovery (PR) and moisture (MC) were developed. Quadratic relationships exist between both PR and PD, and MC. Optimum MC for pellet durability was between 20 and 30% for both 6 mm and 8 mm dies. Μodels eliminate the PD determination process when the MC and PR are known. An approach to simplify and reduce cost of the pelleting process was established.